Effect of dexmedetomidine on evoked‐potential monitoring in patients undergoing brain stem and supratentorial cranial surgery. Issue 8 (12th May 2021) - Pacreu, Susana; Vilà, Esther; Moltó, Luis; Fernández‐Candil, Juan; Fort, Beatriz; Lin, Yiyang; León, Alba
Abstract : Background: Dexmedetomidine is used as adjuvant in total intravenous anaesthesia (TIVA), but there have been few studies concerning its effect on intraoperative neurophysiological monitoring (IONM) during cranial surgery. Our aim was to study the effect of dexmedetomidine on IONM in patients undergoing brain stem and supratentorial cranial surgery. Methods: Two prospective, randomized, double‐blind substudies were conducted. In substudy 1, during TIVA with an infusion of propofol and remifentanil, 10 patients received saline solution (SS) (PR group) and another 10 (PRD group) received dexmedetomidine (0.5 mcg/kg/h). Total dosage of propofol and remifentanil, intensity, latency and amplitude of motor‐evoked potentials following transcranial electrical stimulation (tcMEPs) as well as somatosensory‐evoked potentials (SSEP) were recorded at baseline, 15, 30, 45 minutes, and at the end of surgery. In order to identify differences in the same patient after dexmedetomidine administration, we designed substudy 2 with 20 new patients randomized to two groups. After 30 minutes with TIVA, 10 patients received dexmedetomidine (0.5 mcg/kg/h) and 10 patients SS. The same variables were recorded. Results: In substudy 1, propofol requirements were significantly lower ( P = .004) and tcMEP intensity at the end of surgery was significantly higher in PRD group, but no statistically significant differences were observed for remifentanil requirements, SSEP and tcMEP latency or amplitude. In substudy 2, no differences in any of the variables were identified. Conclusions: The administration of dexmedetomidine at a dosage of 0.5 mg/kg/h may reduce propofol requirements and adversely affect some neuromonitoring variables. However, it can be an alternative on IONM during cranial surgeries. REDEX EudraCT: 2014‐000962‐23